Implementation of the Smart Village Nusantara (SVN) Program in Sambirejo Village, Sleman Regency - Rahmawati, Agustina; Nugroho, Hanantyo Sri; Lestari, Vidia (Universitas Teuku Umar, 2024)
This research will examine implementing the Smart Village Nusantara (SVN) program in the Sambirejo District. This research aims to determine the management and implementation of the village headquarters in implementing the smart village program, the aim of which is to facilitate the sustainable improvement of the welfare of the Sambirejo community. This sub-district, which is famous for its Breksi Cliff, is one of the sub-districts that has become a pilot project for other sub-districts to manage Bumdes and increase Ali Village Income (PADes). This is very different from the period in the 2000s when Sambirejo was even included in the list of the poorest villages in Sleman Regency. This problem is interesting to research because currently, villages have space to manage resources through various innovations after the existence of village law policies, namely Law Number 6 of 2014. A perspective is used to analyze this problem, namely the perspective of public policy implementation. Furthermore, the research method used in this research is a descriptive qualitative method. In the descriptive qualitative method, the factor that must be considered is the validity of the data, where this research uses a data triangulation model. Meanwhile, this research was conducted in Sambirejo Village in Sleman Regency. This research aims to determine the aspects that drive the success of the program and the challenges in implementing the smart village program in Sambirejo District through accelerating the smart economy, smart society, and smart government. It is hoped that this research will be able to produce at least three main findings. First, to what extent are efforts to implement smart villages implemented in the development of Sambirejo. Second, opportunities and challenges in implementing smart villages. Third, recommendations to relevant stakeholders.